2013
DOI: 10.1186/1476-069x-12-76
|View full text |Cite
|
Sign up to set email alerts
|

Association between Perfluoroalkyl substances and thyroid stimulating hormone among pregnant women: a cross-sectional study

Abstract: BackgroundPerfluoroalkyl substances (PFASs) are a group of highly persistent chemicals that are widespread contaminants in wildlife and humans. Exposure to PFAS affects thyroid homeostasis in experimental animals and possibly in humans. The objective of this study was to examine the association between plasma concentrations of PFASs and thyroid stimulating hormone (TSH) among pregnant women.MethodsA total of 903 pregnant women who enrolled in the Norwegian Mother and Child Cohort Study from 2003 to 2004 were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 48 publications
1
55
4
Order By: Relevance
“…Another potential mechanism by which PFASs might have an adverse effect on neurodevelopment is through interference with thyroid hormone signaling. The thyroid hormone plays a role in synaptogenesis and myelination in the developing brain during the prenatal and postnatal periods, and previous studies in human reported associations between exposure to PFASs and thyroid gland disruption (Melzer et al 2010; Wang et al 2014; Wang et al 2013). …”
Section: Discussionmentioning
confidence: 96%
“…Another potential mechanism by which PFASs might have an adverse effect on neurodevelopment is through interference with thyroid hormone signaling. The thyroid hormone plays a role in synaptogenesis and myelination in the developing brain during the prenatal and postnatal periods, and previous studies in human reported associations between exposure to PFASs and thyroid gland disruption (Melzer et al 2010; Wang et al 2014; Wang et al 2013). …”
Section: Discussionmentioning
confidence: 96%
“…In vitro models suggested that PFASs can directly influence neuronal differentiation [101]. PFASs can compete with T4 for binding to transthyretin, a main carrier protein of TH in mammals [102], thus increasing thyroid-stimulating hormone (TSH) and decreasing free thyroxine (fT4) [103105]. Thyroid hormones transferred from the mother to the embryo and fetuses are critical for normal brain development [106], and TH deficiency during gestation may cause cognitive and/or mental disorders [107111].…”
Section: Discussionmentioning
confidence: 99%
“…When assessing individual contaminants, we demonstrated significant associations between PFOS and TSH. Accordingly, PFOS was positively associated with TSH in pregnant women in Norway sampled in 1999–2008 (Wang et al 2013). Further, we demonstrated that PCBs, HCB, and nonachlors were inversely associated with T 3 , T 4 , and FT 4 .…”
Section: Discussionmentioning
confidence: 99%